Hubungan Antara Sikap Dan Perilaku Masyarakat Kecamatan Kalideres Jakarta Barat Terhadap Kejadian Demam Berdarah Dan Tinjauannya Dari Agama Islam - Meylani Nur Arifin (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Dengue fever is a disease spread by the bite of the Aedes aegypti mosquito. Dengue fever is a problem both in Indonesia and in several other countries. World Health Organization (WHO) Indonesia has the highest number of dengue hemorrhagic fever cases in Southeast Asia. This type of research is non-experimental or descriptive quantitative research. Quantitative research is research that requires an activity to collect data then processed and analyzed and then made a presentation of data in terms of the number or volume of objective execution. There are also objectives carried out to prevent dengue fever through Mosquito Control Activities (PSN), including 3M Plus activities such as draining reservoirs, closing reservoirs, burying old items, recycling old items and sowing larvicides, using mosquito nets, using mosquito repellent, planting mosquito repellent plants.